Tourism Situation Analysis of the Locals in Ban Tham Subdristrict, Dok Kham Tai District, Phayao - Gunma, Namfon; Somyaron, Wilawan; Seehamat, Lumyai (Journal of Roi Et Rajabhat University, 2021)
This research aimed to analyze context and assess situations of tourism in Ban Tham subdistrict, Dok Kham Tai district, Phayao province. Qualitative research methodology was applied for this study. The sample was 85 participants, including 16 staff of Ban Tham Municipality, 13 entrepreneurs, 6 community leaders, and 50 local civilians who were selected by purposive sampling. The instruments for data collection were a document analysis form, a semi-structured interview form, and an assessment of tourism situation form. The data were analyzed by content analysis and descriptive writing was utilized to conclude the findings. The result showed that there are plentiful of tourism resources in Ban Tham subdistrict, such as natural attractions, arts and cultures, and the community way of life.